Spatial strategies of firms under Stackelberg competention - Melnikov, S. (Математичне моделювання в економіці, 2018)
The paper explores a spatial duopoly of firms under Stackelberg competition, when one of the firms is a leader in term of product volume. The equilibrium spatial strategies of firms are found. In the process of the analysis of equilibrium stability, it is proved that the transport tariff is a bifurcation parameter for firms. It was found that the change in the central agglomeration strategy to the differentiation strategy occurs at the point of transcritical bifurcation. The conditions for full coverage of the markets for both strategies are defined. It is obtained that the information asymmetry leads to asymmetry of equilibrium locations of firms. It is established that under differentiation strategy, the follower can due to the space factor overcome information asymmetry in the nearest markets and get a profit more than the leader.